2005
DOI: 10.1016/j.fertnstert.2005.04.044
|View full text |Cite
|
Sign up to set email alerts
|

Changes in spermatozoal chromatin packaging and susceptibility to oxidative challenge during aging

Abstract: Objective: Our goal was to test the hypothesis that spermatozoal chromatin packaging changes with age and that aging affects the susceptibility of spermatozoal DNA to oxidative damage. Design: Laboratory study. Setting: Academic facility. Patient(s): Young (4 months) and old (21 months) Brown Norway rats. Intervention(s): Spermatozoa were collected from the cauda epididymidis and were incubated in saline or H 2 O 2 . Main Outcome Measurement(s): Thiols levels, chromatin condensation, DNA susceptibility to acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 74 publications
4
47
1
Order By: Relevance
“…Additionally, a number of studies have demonstrated an age-related increase in sperm cells with double-stranded DNA breaks or poor chromatin packaging [1,4,[26][27][28]. In the current study, it was observed that DNA fragmentation and poor chromatin packaging was significantly higher in OAT patients ≥35 years compared to patients younger than 34 years old.…”
Section: Discussionsupporting
confidence: 51%
“…Additionally, a number of studies have demonstrated an age-related increase in sperm cells with double-stranded DNA breaks or poor chromatin packaging [1,4,[26][27][28]. In the current study, it was observed that DNA fragmentation and poor chromatin packaging was significantly higher in OAT patients ≥35 years compared to patients younger than 34 years old.…”
Section: Discussionsupporting
confidence: 51%
“…Reactive oxygen species (ROS) appear to affect the stability of human sperm DNA and sperm chromatin condensation, which eventually impact sperm function [Zubkova et al 2005]. Furthermore, it has been shown that higher lipid peroxide levels in semen correlates to lower sperm motility [Kao et al 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that the DNA of mice is extremely well protected against oxidative stress and DNA-breaking molecules. Interestingly, rat spermatozoa treated with 2.5 mM H 2 O 2 experienced a high increase in DNA damage compared with control treatments [66]. Further studies on other rodent species could elucidate why the sperm DNA of different rodent species may differ in their resistance to oxidative stress.…”
Section: Discussionmentioning
confidence: 93%